Industrial materials science and engineering - Murr, Lawrence Eugene (Manufacturing engineering and materials processing, 1984)
'Industrial Materials Science and Engineering' provides a broad historical perspectives and current overview of modern materials properties and behavior, emerging materials technologies, materials processes in high-technology industries, and fundamental materials development stategies.